2022
DOI: 10.1177/10598405221124423
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID 19 Pandemic on School Nurses’ Resiliency and Ability to Cope: A Mixed Methods Study in the State of Hawaii

Abstract: This mixed-method study examined school nurses’ experiences during the Coronavirus Disease 2019 pandemic related to role change, psychological feelings, and coping/resiliency in the State of Hawaii. A total of 30 school nurses completed a Brief Resilience Coping Scale plus a series of open-ended questions in January 2022. On the coping scale, over 40% of participants scored high, 52% scored medium, and 7% scored a low resilient/coping level. We did not identify any association between coping level and particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…We also found that burnout levels were slightly higher than those reported in previous studies on healthcare workers ( Tan et al, 2020 ) and clinical nurses ( Xu et al, 2022 ), particularly in the exhaustion domain. However, they are consistent with the study of Hale et al (2022) , which reported that school nurses clearly indicated feeling overwhelmed, exhaustion, and stress during the start of the COVID-19 pandemic. Moreover, prolonged engagement in a job without sufficient support could lead to extra physical, emotional, and affective burdens, thereby resulting in exhaustion due to a long-term consequence of prolonged exposure to COVID-19-related job demands ( Zhou et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also found that burnout levels were slightly higher than those reported in previous studies on healthcare workers ( Tan et al, 2020 ) and clinical nurses ( Xu et al, 2022 ), particularly in the exhaustion domain. However, they are consistent with the study of Hale et al (2022) , which reported that school nurses clearly indicated feeling overwhelmed, exhaustion, and stress during the start of the COVID-19 pandemic. Moreover, prolonged engagement in a job without sufficient support could lead to extra physical, emotional, and affective burdens, thereby resulting in exhaustion due to a long-term consequence of prolonged exposure to COVID-19-related job demands ( Zhou et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…School nurses may experience extra job stress under the heavy workload of conducting infectious disease control tasks in schools within the urgent time frame ( Yim & Kim, 2022 ). Such perceived stressors experienced daily by school nurses can impact their mental health and well-being ( Hale et al, 2022 ; Lee et al, 2021 ).…”
mentioning
confidence: 99%
“…The International Committee of the Red Cross reported 611 incidents of violence, harassment, or stigmatization against healthcare workers, patients, or healthcare facilities between February and July 2020 (Devi, 2020). These findings illustrate that employers of community-based and outpatient healthcare workers, such as school nurses, should also be vigilant and proactive in monitoring for violence against healthcare workers and take steps to ensure a safe work findings of other recent studies (Baker et al, 2023;Hale et al, 2023;Morse et al, 2023;Seo et al, 2023;Um & Choi, 2022;Wilson et al, 2023). Washington school nurses described a series of events, beginning with isolation from administration, decision-making, and planning that led to a lack of resources and equipment, inequitable pay, and an untenable COVID-19-related workload.…”
Section: Discussionmentioning
confidence: 87%
“…The COVID-19 pandemic threatened to further erode the school nursing workforce through new challenges and the amplification of existing demands. School nurses experienced overwhelming demands from added COVID-19 responsibilities that were prioritized above chronic disease management, health screenings, and other school nurse duties (Baker et al, 2023;Best et al, 2023;Cook et al, 2023;Hale et al, 2023;Lowe et al, 2023;Seo et al, 2023;Um & Choi, 2022;Wilson et al, 2023). The added COVID-19 workload was even too much to complete during work hours, leading nurses to work after the school day, on weekends, and holidays with little or no added pay (Merkle et al, 2023;Morse et al, 2023;Wilson et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A mixed methods study examined SNs' experiences related to a role change, psychological feelings, and coping/resiliency during the COVID‐19 pandemic (Hale et al., 2022). Thirty SNs completed a Brief Resilience Coping Scale (Kocalevent et al., 2017) and open‐ended questions on a survey.…”
Section: Introductionmentioning
confidence: 99%